New Correlations for Coal and Biomass Pyrolysis Performances with Coal-Biomass Type Number and Temperature - Yazid Bindar (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
The pyrolysis of coal and biomass is generally reported as the mass yield of released chemicals at various temperatures, pressures, heating rates and coal or biomass type. In this work, a new coal-biomass type number, NCT, is introduced. This number is constructed from the mass fractions of carbon, hydrogen, and oxygen in the ultimate analysis. This number is unique for each coal or biomass type. For 179 different species of coal and biomass from the literature, the volatile matter mass yield can be expressed by the second order polynomial function ln(NCT). This unique correlation allows the effects of the temperature and heating rate on the volatile yield YVY for coal and biomass to be empirically correlated as well. The correlation for the mass fraction of each chemical component in the released volatile matter correlation is obtained from the YVY correlation. The weight factor for some of the components is constant for the variation of NCT, but not for others. The resulted volatile matter and yield correlations are limited to atmospheric pressure, very small particles (less than 0.212 mm) and interpreted for wire-mesh pyrolysis reactor conditions and a nitrogen gas environment.